Impact of in-hospital COVID-19 quarantine policy changes on quality of acute stroke care: a single center experience - Kim, Minkyung; Lee, Keon-Joo; Kim, Seong-Eun; Kim, Hokyu; Han, Jung Hoon; Kim, Han Jun; Oh, Kyungmi; Park, Sung-Jun; Kim, Chi Kyung; Cho, Young-Duck (Frontiers in Neurology, 2025)
IntroductionThe COVID-19 pandemic is known to impact in-hospital processes for acute stroke patients, potentially resulting in delays due to quarantine and screening measures. The purpose of this study was to determine effects of changes in in-hospital quarantine policies on quality of care for acute stroke patients.MethodsHyperacute ischemic stroke patients who were admitted to Korea University Guro Hospital between January 2019 and February 2021 via the emergency department were included in this study. All had neurological symptoms within 6 h before arrival. As a mandatory COVID-19 real-time PCR screening test was implemented in March 2020, changes in quality indicators according to the progress of COVID-19 pandemic and changes in in-hospital quarantine policy, including door-to-image time (DIT), door-to-referral time, door-to-needle time (DNT), door-to-puncture time (DPT), and functional outcomes (discharge and 3-month modified Rankin’s scale) were determined.ResultsA total of 268 hyperacute stroke patients were analyzed. The number of hyperacute stroke patients gradually decreased as the pandemic progressed. Time indicators, including door-to-referral time, DIT, and DPT during the pandemic were increased. When pre-and post-COVID-19 screening epochs were compared, DIT, door-to-neurologist referral time, and DPT showed numerical increases. However, after accounting for potential confounders, a significant delay in DIT was found to be associated with the in-hospital COVID-19 quarantine policy.DiscussionOur study showed that enhancing in-hospital COVID-19 quarantine measures might increase the response time for hyperacute stroke care, suggesting an impact on the quality of care.